IDENTIFIKASI POTENSI ANTIOKSIDAN DALAM MINUMAN COKLAT DARI KAKAO LINDAK (Theobroma cacao L.) DENGAN BERBAGAI CARA PREPARASI: METODE FERRIC REDUCING ANTIOXIDANT POWER (FRAP) - Halim, Florentin Yunita; Marsono, Yustinus; Suprijono, Maria Matoetina (Widya Mandala Surabaya Catholic University, 2013)
Cocoa has been proved to be a source of antioxidant. This study aimed to determine the effect of chocolate drinks preparation to the ability of antioxidants to reduce Ferric Tripyridyl triazine complex (Fe III TPTZ) to Ferro form. This research used a single factor, Chocolate Drinks Preparation Methods consisted of four treatments (P), dissolving the cocoa powder in room temperature water (P1), dissolving cocoa powder in boiled water (P2), dissolving cocoa powders in room temperature water then heated until boiling (P3), and dissolving cocoa powders in room temperature water then heated until boiling using microwave oven (P4). Each treatment was repeated two times. The experiment units were randomized using Randomized Block Design with ability of antioxidants to reduce Ferric Tripyridyl Triazine (Fe III TPTZ) complex to Ferro form as parameter. The effect was analyzed using analysis ANOVA at α = 5% then continued with Duncan Multiple Range Test α = 5% to determine the level of treatment that gives significant difference. The results showed that preparation methods had significant effect on total phenolic contents in chocolate drinks but showed no significant effect on total flavonoid contents ((+)-catechin nor (-)-epicatechin) and the ability of antioxidants to reduce Ferric Tripyridyl triazine complex (Fe III TPTZ) to Ferro form. Total phenolic content of samples was 16,1 – 28,6 mg GAE/ g chocolate powder. Total flavanoid content was 18,8 – 27,4 mg CE/g chocolate powder and 36,0 – 47,3 mg ECE/g chocolate powder. Cacao’s antioxidant capacity to reduce Fe3+ to Fe2+ was 136,2 – 168,5 mM Fe(II)/L.